Analysis of the phytotoxic influence of filtrate, agrolandscape and drinking water by solid municipal wastes landfill in Poltava region - Самойлік, М. С.; Молчанова, А. В. (Scientific Progress & Innovations, 2017)
Growth number of production, the consumer activity of the population, the inefficient use of resources, the limited involvement of secondary resources in production, the lack of effective organizational and environmental incentive mechanisms for recycling waste, the problem of solid domestic wastes has become a global. Proving landfill of solid domestic wastes – a typical example of anthropogenic activity. They are characterized by a number of signs of chemical contamination of soils, surface, ground and underground waters, plant groups, atmospheric air, which are the objects of various environmental research.